Association Between Publicly Funded Contraceptive Services and the Abortion Rate in Texas, 2010–2015. Issue 2 (4th February 2023) - Madison, Anita M.; Powers, Daniel; Maslowsky, Julie; Goyal, Vinita
Abstract : Texas counties with greater abortion-rate declines had more publicly funded contraceptive clinics and served more contraceptive clients than counties with lower abortion-rate declines. Abstract : OBJECTIVE: To evaluate how the availability of contraceptive services was associated with a change in the abortion rate before and after Texas' legislative changes to the family planning budget in 2011 and abortion access in 2013. METHODS: In this cross-sectional study, we obtained 2010 and 2015 data on contraceptive provision (number of publicly funded clinics and number of contraceptive clients served per 1, 000 reproductive-aged women) from the Guttmacher Institute and county-level abortion data from the Texas Department of State Health Services. We categorized counties as having an abortion rate that increased or declined less than the national rate between 2010 and 2015 ( low-decline counties ) compared with those having an abortion rate that declined equal to or greater than the national rate between 2010 and 2015 ( high-decline counties ). We evaluated differences in contraceptive provision between high-decline and low-decline counties and evaluated county characteristics (racial and ethnic composition, unemployment, poverty, uninsured, education, distance to an abortion clinic, deliveries covered by Medicaid, and Catholic hospital marketplace dominance) as potential confounders. RESULTS: Of 157 counties that had at least one contraceptive clinic in either 2010 or 2015, 49 were low-decline counties and 108 were high-decline counties. Although the total number of publicly funded family planning clinics increased by 10.8%, there was a 4.7% decrease in the total number of contraceptive clients served statewide. Compared with low-decline counties, high-decline counties had a higher median number of contraceptive clients served per 1, 000 women aged 18–44 years (31.9 vs 60.7, P <.05) in 2015. Between 2010 and 2015, the abortion rate decreased 19.7% for each 1.0% increase in contraceptive clients served. CONCLUSION: Texas counties with higher abortion-rate declines had more publicly funded contraceptive clinics and served more contraceptive clients than counties with lower declines, which may indicate the importance of greater access to publicly funded contraceptive services.